3D printing of conducting polymers - Hyunwoo Yuk (Nature Portfolio, 2020)
Conducting polymers are promising materials for diverse applications but the fabrication of conducting polymers mostly relies on conventional fabrication techniques. Here the authors introduce a high performance 3D printable conducting polymer ink to take full advantage of advanced 3D printing.